2013 IFPRI Annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
After decades on the sidelines, agriculture and food security have recently found their place at the top of the global development and policy agendas. In a world where 900 million people are undernourished and 2 billion are micronutrient deficient, ensuring access to nutritious foods is critical to lifting more than 1 billion poor people out of poverty.